Limited arbitrage and short sales restrictions: evidence from the options markets - Ofek, Eli; Richardson, Matthew; Whitelaw, Robert F. (Journal of Financial Economics, 2004)
We investigate empirically the well-known put–call parity no-arbitrage relation in the presence of short sales restrictions. Violations of put–call parity are asymmetric in the direction of short sales constraints, and their magnitudes are strongly related to the cost and difficulty of short selling. These violations are also related to both the maturity of the option and the level of valuations in the stock market, consistent with a behavioral finance theory of over-optimistic stock investors and market segmentation. Moreover, both the size of put–call parity violations and the cost of short selling are significant predictors of future returns for individual stocks.